Dividend Stickiness, Debt Covenants, and Earnings Management - Kim, Jaewoo; Lee, Kyeong Hun; Lie, Erik (Contemporary Accounting Research, 2017)
Abstract Consistent with the notion that dividends are very sticky, Daniel, Denis, and Naveen ( ) report evidence that firms manage earnings upward when pre‐managed earnings are expected to fall short of dividend payments. However, we find that this evidence is not robust when controlling for firms' tendency to manage earnings upward to avoid reporting earnings declines; only firms with high leverage exhibit a statistically weak tendency to manage earnings to close deficits of pre‐managed earnings relative to dividends. We further report that the decision to cut dividends depends on whether reported earnings fall short of past dividends, but not on earnings management that eliminates a shortfall in pre‐managed earnings relative to dividend payments. Overall, our evidence suggests that firms that face dividend constraints are more likely to cut dividends than to manage earnings to avoid dividend cuts.